Direct Immobilization of Coagulation Factor VIII on Au/Fe3O4 Shell/Core Magnetic Nanoparticles for Analytical Application - Sharafi, Zeinab; Ranjbari, Javad; Javidi, Jaber; Nafissi-Varcheh, Nastaran; Tabarzad, Maryam (Trends in Peptide and Protein Sciences, 2016)
Protein-coated nanoparticles have diverse applications in biomedical science. The protein hydrophobic domains or surface electrostatic charge conducts adsorption of proteins to different surfaces. This property can be customized to immobilize specific molecules on solid supports for experimental screenings or purification processes. To develop highly selective affinity ligands—such as aptamers—against specific protein targets, protein-coated magnetic particles have been successfully applied. This approach could be highly efficient in affinity ligand development against coagulation factor VIII.In this study, magnetic nanoparticles were prepared by co-precipitation method and, then, a gold coating was run on the MNPs’ surface. The gold coating could add some attractive specifications to the protein immobilized nanoparticles during the aptamer selection process, such as simultaneous affinity determination of aptameric oligonucleotides by fluorescence-based methods. The gold surface has been indicated as a specific feature for covalent binding to the sulphur functional groups of various molecules. In proteins, sulphur units of cysteine or methionine might be bound covalently to the gold surface. In addition, nonspecific and non-covalent attachment of proteins to the gold particles may be performed. Therefore, a series of samples containing different mass ratios of protein to gold magnetic nanoparticles (GMNPs) were evaluated to find the best conditions for coagulation factor VIII immobilization. The results showed that the best condition for high coating efficiency was 48 h incubation at 4 ºC of protein and GMNPs with a mass ratio of 0.5% in PBS 25mM, with pH=7 as binding buffer. Highlights: Magnetic nanoparticles are the most attractive nanostructures in biomedical and bio-analytical fields. The protein coating on MNPs has been found to have wide clinical and analytical applications. Coagulation factor VIII (FVIII) is a valuable therapeutic human protein in the market. Attachment of a large protein like F VIII to GMNPs is affected by various environmental factors.